ANALYSIS OF THE DISADVANTAGES AND ADVANTAGES OF THE MODERN HRM SYSTEMS FOR OPTIMIZING THE FUNCTIONING OF ENTERPRISES - AZAROVA, Anzhelika; MIRONOVA, Yuliia; SHIYAN, Anatolii; YARMOLA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article is devoted to the analysis of the advantages and disadvantages of modern HRM systems for optimizing the work of enterprises. Among the most common HRM information systems, such as built-in, cloud and mobile systems, «Zoho People», «OrangeHRM», «CakeHR», «Workable», «BambooHR», «SAP SuccessFactors», «Workday HCM», «DeloPro», «HugeProfit», «ISpro», «Scala HR», «Axapta HR Management», «IRenaissance Human Resources / Payroll», «Hurma System», "Vchasno» were researched. A detailed study of the disadvantages and advantages of the mentioned HRM systems helps to determine the optimal system for researched enterprise (organization) according to the specifics of its activity, opportunities, and potential. The authors note that the successful implementation of HRM systems requires interaction between the IT department and the personnel management department, as well as a clear understanding of the organization's needs and goals. The article proves that HRM systems are a necessary tool for optimizing the work of enterprises, but their implementation should be carried out taking into account the specific needs and capabilities of the organization.
Keywords: HRM system; personnel management; advantages and disadvantages of HRM systems; optimization of enterprise operations